Influence of medical student career aims on ophthalmic surgical simulator performance (part of the international forum for ophthalmic simulation studies). Issue 3 (5th August 2015) - Gillan, S N; Okhravi, N; O'Sullivan, F; Sullivan, P; Viswanathan, A; Saleh, G M
Abstract : Background: To evaluate whether medical students who have expressed a strong desire to pursue ophthalmology as a career perform simulated ophthalmic surgical tasks to a higher level than medical students whose interests lie elsewhere. Methods: All participants were fourth or fifth year students at University College London (UCL) Medical School, London, UK. One cohort was recruited from the Moorfields Academy, an ophthalmic forum designed to enhance collaboration and innovation within the specialty. These students were therefore seen as highly motivated, expressing a desire to pursue a career in ophthalmology. The other cohort of students was invited to participate during their fourth year UCL Ophthalmology attachment, but expressed interest in non-ophthalmic disciplines. Participants carried out a single attempt of three modules on the Eyesi Surgical Simulator, and total and mean scores were calculated out of 100. Results: 13 academy and 15 non-academy students were enrolled. The overall mean scores were 51/100 for the academy group, range 0–97, and 45.5/100 for the non-academy group, range 0–90 (p=0.49). Scores for precision testing, forceps training and capsulorrhexis training for academy versus non-academy were 45.8 versus 37.8 (p=0.61), 57.1 versus 52.3 (p=0.8) and 50.2 versus 46.4 (p=0.55), respectively. Conclusions: This study is the first to suggest that medical students with a strong career interest in ophthalmology do not perform microsurgical tasks to a higher level than medical students who have no goal in this area. This also indicates variation in scores between novices, which may serve as a pitfall in the use of simulators as a tool for entry into training.